2006
DOI: 10.1159/000093678
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vitamin E-Coated Membrane in Reducing Advanced Glycation End Products in Hemodialysis Patients: A Pilot Study

Abstract: Introduction: Advanced glycation end products (AGEs) are markers of oxidative stress. Aims: To assess if a vitamin-E-coated dialyzer affects plasma AGE levels and endothelial function in hemodialysis patients. Methods: 16 patients were dialyzed with a synthetic modified cellulose membrane (SMC, n = 8) or a vitamin E-coated dialyzer (n = 8), respectively. At week 32 endothelial function was determined as brachial artery flow-mediated dilatation (FMD). Total AGEs, free pentosidine (FP), protein-bound pentosidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 62 publications
0
31
0
Order By: Relevance
“…The effect of vitamin E-coated dialyzer on HB level was assessed in six trials, 8,14,15,21,23,25 this meta-analysis showed a nonsignificant increase in HB level compared with that of control (MD, À0.03; 95% CI, À0.18 to 0.13; p ¼ 0.74; Figure 3), with significant heterogeneity between studies (p ¼ 0.06; I 2 ¼ 50%). Six studies reported the EPO dose as mean and standard deviation, 8,[13][14][15]23,25 the fixed model was performed for meta-analysis.…”
Section: Effects On Renal Anemiamentioning
confidence: 96%
See 3 more Smart Citations
“…The effect of vitamin E-coated dialyzer on HB level was assessed in six trials, 8,14,15,21,23,25 this meta-analysis showed a nonsignificant increase in HB level compared with that of control (MD, À0.03; 95% CI, À0.18 to 0.13; p ¼ 0.74; Figure 3), with significant heterogeneity between studies (p ¼ 0.06; I 2 ¼ 50%). Six studies reported the EPO dose as mean and standard deviation, 8,[13][14][15]23,25 the fixed model was performed for meta-analysis.…”
Section: Effects On Renal Anemiamentioning
confidence: 96%
“…Among them, duplicate records, non-RCTs or quasi-RCTs, review and letter, article not in English, other intervention and concerning other outcome were excluded. After the progressive selection process, 14 eligibility studies 1,8,[13][14][15][16][21][22][23][24][25][26][27][28] including five crossover and nine parallel-arm trials were included in this meta-analysis ( Figure 1). …”
Section: Selection and Identification Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A larger multicenter study (172 patients) reported by Cruz et al, 2008, confirmed that the impact of Excebrane dialyzers on anemia parameters was better than that of other high-flux biocompatible dialyzer membranes, including cellulose acetate, polysulfone, and polymethylmethacrylate. Other reports demonstrated positive effects such as (1) decreased oxidative stress (Tarng et al, 2000;Miyazaki et al, 2000;Clermont et al, 2001;Westhuyzen et al, 2003;Bufano et al, 2004;Mydlik et al, 2004;Calò et al, 2004;Yang et al, 2006;and Odetti et al, 2006), (2) suppression of leukocyte activation (Omata et al, 2000;Zaluska et al, 2001;Pertosa et al, 2002;Tsuruoka et al, 2002;Libetta et al, 2004;and Kojima et al, 2005), (3) dosage reduction of anticoagulants (Huraib et al, 2000), (4) improved biocompatibility (Yoshida et al, 2002), and (5) decreased levels of advanced glycation end products (AGEs) (Baragetti et al, 2006). Moreover, a recent study reported by Kirmizis D et al, 2010, showed that the levels of inflammatory markers such as C-reactive protein (CRP), interleukin (IL)-6, and soluble intercellular adhesion molecule (sICAM)-1 in 35 patients treated with Excebrane were lower than those in the baseline evaluation carried out with conventional low-or middle-flux dialyzers.…”
Section: Clinical Outcomesmentioning
confidence: 99%